A STUDY ON IMPACT OF TOURISM IN TAMIL NADU - Dr. S. Praveenkumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Tourism plays an important part in humanity’s economic and cultural growth. Tourism is a mix of events, facilities that include transport, lodging, and restaurantsfor individuals or groups who travel away from their homes to have a travel experience, accommodation and other tourism facilities. It includes all service providers and it is the whole travel, hotel, transport and all other components of the world industry that meets the needs and desires of travellers, including promotion. Tourism is described by the Tamil Nadu Tourism Society as their stay at each destination, temporary short-term travel of individuals to destinations beyond the locations where they normally live and work and their activities. It also includes facilities such as lodging, restaurants, cafes, bars and canteens, as well as tour operators and travel agencies. The goal of the research was to examine the effect of tourism in Tamil Nadu.